Tumor Burden and Intraosseous Metabolic Activity as Predictors of Bone Marrow Failure during Radioisotope Therapy in Metastasized Prostate Cancer Patients. (25th December 2017) - Fiz, Francesco; Sahbai, Samine; Campi, Cristina; Weissinger, Matthias; Dittmann, Helmut; Marini, Cecilia; Piana, Michele; Sambuceti, Gianmario; la Fougère, Christian
Abstract : Rationale . Radium-223-Dichloride (Ra-223) is an alpha-emitter, used to treat bone metastases. Patients with high metastatic burden and/or with increased trabecular bone uptake could present a higher incidence of hematologic toxicity. We hypothesized that these two factors are predictors of bone marrow failure. Material and Methods . A computer algorithm discriminated between trabecular bone (B V o l ) and tumor metastases (M V o l ) within pretherapeutic whole-body skeletal SPECT/CT (N = 47 ). The program calculated the metastatic invasion percent (INV%) as the M V o l / ( M V o l + B V o l ) ratio and extracted the B V o l mean counts. B V o l counts were correlated to % drop of hemoglobin (Hb), leukocytes (WBC), and platelets (PLT) after 3/6 Ra-223 cycles. Patient-specific and computational-derived parameters were tested as predictors of hematologic toxicity with MANOVA. Results . B V o l counts correlated with drop of Hb (R = 0, 65, p < 0.01 ) and PLT (R = 0, 45, p < 0.01 ). Appendicular B V o l counts showed a better correlation (p < 0.05, p < 0.01, and p < 0.001 for Hb, WBC, and PLT, resp.). INV% directly correlated with B V o l counts (R = 0.68, p < 0.001 ). At MANOVA, grade III/IV toxicity was predicted by INV% (p < 0.01 ), by long-bone invasion (p < 0.005 ), and by B V o l counts (p < 0.05 ). Conclusions . In patients with significant bone tumor burden, degree of bone invasion and trabecular bone uptake are predictors of subsequent bone marrow failure.